PENERAPAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 016 TALANG PRINGJAYA KECAMATAN RAKITKULIM KABUPATEN INDRAGIRI HULU - Mastini Rahayu; Jesi Alexander Alim; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to improve learning outcomes fifth grade science students of SDN 016 Talang Pringjaya tahun 2014/2015 teachings. Subjects were students of class V SDN 016 Talang Pringjaya dengan number of students as many as 20 students. This research is a form of action research collaborative with two cycles. The research data students learning outcomes of students has increased, the value of acquired activiti improvement es of teachers in the first cycle with the average was 72.72% and the second cycle increased by an average of 89.77% of students in the clas V of activity with an average of 71.59% and on the second cycle increased by an average of 88.63% Data from the study experienced improvement wherein prior to the action learning model Kontestual on the basis of the complete score of 4 people with an average value of 57.25. siklus I experienced improvement, with the average 72.25 and second cycle students' average score was 82.25. thus it can be concluded that the hypothesis in this study is "if applied learning model Kontestual it can increase learning outcomes fifth grade science students SDN 016 TalangPringjaya.Keywords : Contextual, IPA Learning Outcomes